Corporate Performance Management ARIS in Practice - Scheer, August-Wilhelm; Jost, Wolfram; Heß, Helge; Kronz, Andreas (Springer Berlin Heidelberg : Imprint: Springer, 2006)
Corporate Performance Management (CPM) is a basic approach which examines the relationship between corporate performance and process optimization. How to successfully introduce CPM in practice is demonstrated through project reports from E.ON, British Telecom, Credit Suisse and Vodafone among others. The methods and tools presented here guarantee a continuous and automated monitoring of the corporate performance and enable Business Process Excellence to be permanently established in the company by company-internal and company-external benchmarking. The articles in this book focus on the use of the ARIS Controlling Platform developed by IDS Scheer.